2021
DOI: 10.1002/adsc.202100697
|View full text |Cite
|
Sign up to set email alerts
|

Domino Ring‐Opening of N‐Tosyl Vinylaziridines Triggered by Aryne Diels‐Alder Reaction

Abstract: The reactivity of N‐tosyl vinylaziridines toward arynes has been demonstrated under mild and transition‐metal‐free conditions to yield 2‐(phenanthren‐9‐yl)ethan‐1‐sulfamides in moderate to good yields. The selective synthesis of N‐H and N‐aryl products was accomplished using CsF in MeCN and KF/18‐C‐6 in 1,4‐dioxane, respectively. This cascade process involves a sequential Diels‐Alder reaction, ring‐opening aromatization, ene‐reaction, and selective N‐arylation reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…27 A further aryne cascade process employing an alkene ene reaction was recently reported by Liu et al (Scheme 8c & d). 28 Upon exposure to excess aryne, N-tosyl vinylaziridines 38 undergo a sequential Diels-Alder cycloaddition, ring-opening aromatisation, ene reaction and final N-arylation to afford 2-(phenanthrene-9-yl)ethan-1-sulfamides 40. It was found that switching reaction conditions from CsF in acetonitrile to KF and 18-crown-6 ether in 1,4-dioxane prevented the final N-arylation stage.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…27 A further aryne cascade process employing an alkene ene reaction was recently reported by Liu et al (Scheme 8c & d). 28 Upon exposure to excess aryne, N-tosyl vinylaziridines 38 undergo a sequential Diels-Alder cycloaddition, ring-opening aromatisation, ene reaction and final N-arylation to afford 2-(phenanthrene-9-yl)ethan-1-sulfamides 40. It was found that switching reaction conditions from CsF in acetonitrile to KF and 18-crown-6 ether in 1,4-dioxane prevented the final N-arylation stage.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Elsewhere, the groups of Minuti, Biju, Chenoweth, and Liu have reported alkene ene reactions involving larger polycyclic hydrocarbon systems. [25][26][27][28] In 1999, Minuti et al used benzyne, generated from diazotisation and subsequent thermal decomposition of anthranilic acid, to produce an arylated pentahelicene. 25 In 2014, Biju and coworkers treated a range of styrenes 32 with o-trimethylsilylaryl triflate 20, in the presence of a fluoride source, to furnish 9-aryldihydrophenanthrenes 34 through the incorporation of two equivalents of aryne (Scheme 8a).…”
Section: Short Review Synthesismentioning
confidence: 99%